2014
DOI: 10.5539/ies.v7n4p120
|View full text |Cite
|
Sign up to set email alerts
|

Visibility and Citation Impact

Abstract: The number of publications is the first criteria for assessing a researcher output. However, the main measurement for author productivity is the number of citations, and citations are typically related to the paper's visibility. In this paper, the relationship between article visibility and the number of citations is investigated. A case study of two researchers who are using publication marketing tools confirmed that the article visibility will greatly improve the citation impact. Some strategies to make the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 35 publications
0
36
0
4
Order By: Relevance
“…To recognize the research trends, bibliometric methods are usually used to evaluate scientific manuscripts [18,19]. Bibliometric methods have been used to measure scientific progress in many disciplines of science and engineering, and are a common research instrument for the systematic analysis of publications [20][21][22][23][24]. In this research, bibliometric analysis is employed in the field of "big data".…”
Section: Introductionmentioning
confidence: 99%
“…To recognize the research trends, bibliometric methods are usually used to evaluate scientific manuscripts [18,19]. Bibliometric methods have been used to measure scientific progress in many disciplines of science and engineering, and are a common research instrument for the systematic analysis of publications [20][21][22][23][24]. In this research, bibliometric analysis is employed in the field of "big data".…”
Section: Introductionmentioning
confidence: 99%
“…Nader Ale Ebrahim et al (2014) based on a case study confirmed that the article visibility will greatly improve the citation impact. The journal visibility has an important influence on the journal citation impact (Yue & Wilson, 2004).…”
Section: Visibility and Citation Impactmentioning
confidence: 94%
“…The number of citations will be limited to the versions of the published article on the web. The literature has shown increased visibility by making research outputs available through open access repositories, wider access results and higher citation impact (Nader Ale Ebrahim et al, 2014;Amancio, Oliveira Jr, & da Fontoura Costa, 2012;Antelman, 2004;Ertürk & Şengül, 2012;Hardy, Oppenheim, Brody, & Hitchcock, 2005). A paper has greater chance of becoming highly cited whenever it has more visibility (Nader Ale Egghe, Guns, & Rousseau, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Igualmente, Ale Ebrahim et al (2014) estudiaron el caso de dos investigadores que utilizan herramientas de marketing para sus publicaciones, encontrando evidencia de que la visibilidad artículo mejora en gran medida el impacto, medido por la citación. A su vez, el trabajo de Abramo et al (2014) analizó en qué medida los científicos italianos más productivos logran artículos muy citados y qué porcentaje de los artículos más citados se logra por los científicos que son los más productivos en Web of Science.…”
Section: Conclusionesunclassified